Interface Interactions of the Bowman–Birk Inhibitor BTCI in a Ternary Complex with Trypsin and Chymotrypsin Evaluated by Semiempirical Quantum Mechanical Calculations. Issue 37 (24th August 2018) - Honda, Diego Elias; Martins, João Batista Lopes; Ventura, Manuel Mateus; Eyrilmez, Saltuk Mustafa; Lepšík, Martin; Hobza, Pavel; Pecina, Adam; de Freitas, Sonia Maria
Abstract : Black‐eyed pea trypsin and chymotrypsin inhibitor (BTCI) is a small protein from Bowman–Birk protease inhibitor family, which simultaneously inhibits trypsin and chymotrypsin. Through the inhibition of trypsin‐ and chymotrypsin‐like sites on the 20S subunit of human proteasome, BTCI acts as a potent anticarcinogenic agent inducing apoptosis in breast cancer cells. Because of the lack of crystallographic information of the BTCI‐proteasome complex, we analyze here the BTCI‐chymotrypsin and BTCI‐trypsin interfaces using computations. We adopt the corrected semiempirical quantum‐mechanical methods in combination with implicit description of the water environment. Firstly, we carefully check the representativeness of smaller systems by fragmentation and analyzing the convergence of the overall interaction energies. Then, we use the "virtual glycine scan" technique to understand the binary complex formation, identifying the most contributing amino acid side chains in the interfaces. Besides detailed quantification of all important residue contributions, the importance of Lys26 and Phe53 in the BTCI and Asp186 (trypsin) and Ser195 (chymotrypsin) residues is confirmed. In summary, we have worked out an accurate and efficient in silico protocol for protein–protein interfaces, which can be later used for studying the inhibition of 20S proteasome. Abstract : We describe the interfaces of the Bowman–Birk inhibitor (BTCI) with proteases trypsin and chymotrypsin by semiempirical quantum‐mechanical methods and give an implicit description of the water environment. The importance of amino acids at the interfaces, for example Lys26 and Phe53 in the BTCI and Asp186 (trypsin) and Ser195 (chymotrypsin), was identified and the side‐chain contributions were quantified.